2014
DOI: 10.2527/jas.2013-7203
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of growth promoting technologies on performance of grazing steers and economics of the wheat pasture enterprise1

Abstract: This research was designed to evaluate the effect of monensin (Elanco Animal Health, Greenfield, IN) supplementation via mineral or pressed protein block with or without a growth-promoting implant on performance of steers grazing wheat pasture in Arkansas over 2 yr. Preconditioned steers (n = 360, BW = 238 ± 5.1 kg) grazed 15 1.6-ha wheat pastures in the fall (n = 60 steers each fall, stocking rate of 2.5 steers/ha) or 30 0.8-ha wheat pastures in the spring (n = 120 steers each spring, stocking rate of 5 steer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
0
19
0
5
Order By: Relevance
“…Mainly because monensin could improve energetic efficiency in the cattle through increased propionic acid production and a reduction in methane production (Erasmus et al, 2008;Neumann et al, 2018). Although the use of virginiamycin as growth promoter for grazing animals is recent, studies have shown that their inclusion in supplements may increase weight gain in grazing animals and improve the efficiency of supplementation programs through increased utilization of nutrients modulating ruminal fermentation (Salinas-Chavira et al, 2009;Nuñez et al, 2013;Beck et al, 2014). The use of monensin and virginiamycin association in beef cattle supplements, to our knowledge, is not yet fully characterized; however, this combination has the potential to maximize nutrient absorption in the rumen and increase animal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly because monensin could improve energetic efficiency in the cattle through increased propionic acid production and a reduction in methane production (Erasmus et al, 2008;Neumann et al, 2018). Although the use of virginiamycin as growth promoter for grazing animals is recent, studies have shown that their inclusion in supplements may increase weight gain in grazing animals and improve the efficiency of supplementation programs through increased utilization of nutrients modulating ruminal fermentation (Salinas-Chavira et al, 2009;Nuñez et al, 2013;Beck et al, 2014). The use of monensin and virginiamycin association in beef cattle supplements, to our knowledge, is not yet fully characterized; however, this combination has the potential to maximize nutrient absorption in the rumen and increase animal performance.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Bagley et al (1988) reported that salinomycin inclusion into a mineral mixture decreased the mineral intake of beef steers from 131 to 65 g/d. Similarly, Beck et al (2014) reported that steers offered a mineral supplement containing monensin had a reduced supplement intake compared with nonsupplemented cohorts (160 vs. 100 g/d, respectively). Lastly, Reffett-Stabel et al (1989) demonstrated that lasalocid and salinomycin supplementation into a mineral mixture to grazing Angus steers decreased the mineral consumption when compared with nonsupplemented cohorts.…”
Section: Resultsmentioning
confidence: 95%
“…Legenda: ¹ CON: mistura mineral sem aditivo; 1800: inclusão de 1800 mg de narasina/kg de mistura mineral; 2750: inclusão de 2750 mg de narasina/kg de mistura mineral; PROT: Suplemento proteinado sem aditivo; PROT 360: inclusão de 360 mg de narasina/kg de suplemento proteinado; ² EPM: erro padrão da média; ³ Contrastes ortogonais, I: CON vs 1800 e 2750, II: 1800 vs 2750, III: CON, 1800 e 2750 vs PROT e PROT 360, IV: PROT vs PROT 360. (BECK et al, 2014;FIESER et al, 2007). Para o presente estudo o produto foi produzido sem a inclusão da monensina, o que pode ter afetado a capacidade de autorregulação de consumo do suplemento, apresentando assim uma ingestão superior a esperada.…”
Section: Análises Estatísticasunclassified